2010
DOI: 10.1111/j.1365-2583.2010.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning, homology modelling and evolutionary insights into novel endogenous cellulases of the borer beetleOncideres albomarginata chamela(Cerambycidae)

Abstract: Novel endogenous cDNAs of beta-1, 4-endoglucanases (Oa-EGase I and Oa-EGase II) were cloned from the cerambycid beetle Oncideres albomarginata chamela. Oa-EGase I- and Oa-EGase II-deduced proteins and three-dimensional structures possess all features, including general architecture, signature motifs and catalytic domains, of glycosyl hydrolase families 5 and 45 (GHF5 and GHF45) and also share high levels of homology with other beetle cellulases. Total carboxymethylcellulase activity of O. a. chamela was 208.13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 70 publications
1
30
0
Order By: Relevance
“…One of the most striking discoveries in the midgut transcriptome was the presence of six GH 5 cellulase unigenes, which all had highest scoring BLASTP alignments to GH 5 endo-β-1,4 glucanases previously detected in the guts of other wood-feeding cerambycid beetles. Recombinant protein expression assays revealed that cellulases associated with other cerambycids (e.g., Apriona germari , Oncideres albomarginata chamela , and Psacothea hilaris ) catalyzed the release of cello-oligomers from crystalline cellulose [26, 27, 40]. These were not flagged as transcript isoforms by Trinity, suggesting that genes encoding cellulases are represented in multiple copies in the A. glabripennis genome.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most striking discoveries in the midgut transcriptome was the presence of six GH 5 cellulase unigenes, which all had highest scoring BLASTP alignments to GH 5 endo-β-1,4 glucanases previously detected in the guts of other wood-feeding cerambycid beetles. Recombinant protein expression assays revealed that cellulases associated with other cerambycids (e.g., Apriona germari , Oncideres albomarginata chamela , and Psacothea hilaris ) catalyzed the release of cello-oligomers from crystalline cellulose [26, 27, 40]. These were not flagged as transcript isoforms by Trinity, suggesting that genes encoding cellulases are represented in multiple copies in the A. glabripennis genome.…”
Section: Resultsmentioning
confidence: 99%
“…Four GH families (GH5, GH7, GH9, and GH45) encoding ENGs and CBHs have been identified in metazoans. Sequence analysis and intron positioning suggest that genes encoding GH7 (described in crustaceans (King et al, 2010)) and GH9 enzymes were present at an early stage of animal evolution, perhaps in the common ancestor of the bilaterians (Lo et al, 2003) or even in very early eukaryotes (Davison and Blaxter, 2005), while the GH5 and GH45 families seem to have been acquired later by HGT in a variety of invertebrates (Scholl et al, 2003;Kikuchi et al, 2004;Calderón-Cortés et al, 2010;Watanabe and Tokuda, 2010;Todaka et al, 2010;Flot et al, 2013;Valencia et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Once thought to be limited to microbes, endogenous (symbiont-independent) PCWDE production has since been found throughout the Animalia. In particular, cellulase (beta-1,4-endoglucanase; Enzyme Commission: 3.2.1.4) genes from the Glycoside Hydrolase family 9 (GH9) are now believed to have existed in the ancestor of all Metazoan life [20, 21] as opposed to having been repeatedly acquired from microbes via horizontal gene transfer, as is thought to be origin of GH45 and GH48 cellulases in beetles [22, 23]. Among insects, endogenous cellulases have been found in lower and higher termites, cockroaches, crickets, beetles [2124], a firebrat [25], a springtail [26], and, recently, the phasmids.…”
Section: Introductionmentioning
confidence: 99%